2015
DOI: 10.1186/s12937-016-0135-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the influence of 25-hydroxyvitamin D on disease progression and survival in pancreatic cancer

Abstract: BackgroundVitamin D deficiency is implicated in neoplastic processes in multiple organs, including the pancreas. While animal and human data have established a relationship between serum vitamin D (25(OH)D) and the development of pancreatic cancer, few studies have examined the effects of 25(OH)D on time to progression (TTP) and overall survival (OS) in this patient population. We hypothesize that lower baseline serum concentrations (BSC) of 25(OH)D will be associated with decreased TTP and OS.MethodsThis retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Five studies on pancreatic cancer mortality in relation to plasma 25(OH)D levels were published between 2013 and 2016, and involved a total of 1613 patients [ 19 , 21 , 22 , 25 , 28 ] (Table 1 ). Of these five studies, four were conducted in the United States and one in Germany.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies on pancreatic cancer mortality in relation to plasma 25(OH)D levels were published between 2013 and 2016, and involved a total of 1613 patients [ 19 , 21 , 22 , 25 , 28 ] (Table 1 ). Of these five studies, four were conducted in the United States and one in Germany.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies assessed the association between plasma 25(OH)D levels and pancreatic cancer mortality [ 19 , 21 , 22 , 25 , 28 ]. Our results indicated that the high versus the low plasma 25(OH)D levels was significantly associated with reduced pancreatic cancer mortality without significant heterogeneity (HR=0.81, 95% CI=0.68–0.96, I 2 =43.0%; Figure 2 ), and the result of Begg's and Egger's tests showed no evidence of publication bias ( P Begg's = 1.00, P Egger's = 0.80, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After resection, reported nutritional deficiencies include fat‐soluble vitamins A, D, and E, vitamins B12 and B6, iron, zinc, selenium, biotin, and copper. None of these can be considered diagnostic of malnutrition; however, vitamin D deficiency has been reported in patients with PC and may contribute to poor outcomes . These findings were concluded from retrospective analysis, and it is not clear whether vitamin D supplementation improves outcomes.…”
Section: Assessment Of Pawlmentioning
confidence: 95%
“…An increased risk for pancreatic cancer with higher vitamin D levels has been found among heavy smokers 77 . Survivorship has been examined, as a retrospective study completed by McGovern and colleagues did not find any association between vitamin D concentrations and disease progression or survival in patients with pancreatic cancer between the highest and lowest quintiles (<20 and >60 ng/mL) 78 . No studies have been completed examining the role of supplementation and pancreatic cancer risk or outcomes once diagnosed.…”
Section: Vitamin Dmentioning
confidence: 99%